Chondrocyte primary cilium is mechanosensitive and responds to low-intensity-ultrasound by altering its length and orientation. (October 2017) - Subramanian, Anuradha; Budhiraja, Gaurav; Sahu, Neety
Abstract: The primary cilium has been implicated in mechanotransduction, however, its mechanosensory role in transducing signals under low-intensity ultrasound (LIUS) which has the potential to repair fractures and cartilage, remains uninvestigated. This study examined the impact of continuous-wave US, at the cell resonance frequency of 5.0 MHz and pressure amplitude of either 14 or 60 kPa, on the incidence, length and orientation of primary cilium in bovine articular chondrocytes. Visualization of primary cilium with acetylated α-tubulin staining demonstrated that the primary cilium was elongated, bent under US and these changes were reversible. Basal expression of phospho-ERK1/2 was lower in deciliated chondrocytes, thus implicating the role for the primary cilium in transducing signals via the MAPK/ERK pathway. This study demonstrates that the chondrocyte primary cilium is mechanosensitive and responds to US by altering its length and orientation.